Improving End-User Trust in the Quality of Commercial Probiotic Products - Jackson, Scott A.; Schoeni, Jean L.; Vegge, Christina; Pane, Marco; Stahl, Buffy; Bradley, Michael; Goldman, Virginia S.; Burguière, Pierre; Atwater, John B.; Sanders, Mary Ellen (Frontiers in Microbiology, 2019)
In a rapidly growing global probiotic market, end-users have difficulty distinguishing between high quality and poor quality products. This threatens consumer and healthcare provider trust in probiotic products. To address this problem, we recommend that companies undergo third-party evaluations that certify probiotic quality and label accuracy. In order to communicate about product quality to end-users, indication of certification on product labels is helpful, although not all manufacturers choose to do so. Herein we discuss: third-party certification, the process of setting standards for identity, purity, and quantification of probiotics; some emerging methodologies useful for quality assessment; and some technical challenges unique to managing quality of live microbial products. This review provides insights of an expert panel engaged in this process and aims to update the reader on relevant current scientific methodologies. Establishing validated methodologies for all aspects of quality assessment is an essential component of this process and can be facilitated by established organizations, such as United States Pharmacopeia. Emerging methodologies including whole genome sequencing and flow cytometry are poised to play important roles in these processes.